Regions enriched for DNA repeats in chromosomes of Macrostomum mirumnovem, a species with a recent Whole Genome Duplication - K. S. Zadesenets; N. B. Rubtsov (Вавиловский журнал генетики и селекции)
The free-living flatworm Macrostomum mirumnovem is a neopolyploid species whose genome underwent a recent Whole Genome Duplication (WGD). In the result of chromosome fusions of the ancient haploid chromosome set, large metacentric chromosomes were formed. In addition to three pairs of small metacentrics, the current karyotype of M. mirumnovem contains two pairs of large metacentric chromosomes, MMI1 and MMI2. The generation of microdissected DNA libraries enriched for DNA repeats followed by DNA probe preparation and fluorescent in situ hybridization (FISH) were performed. The DNA probes obtained marked chromosome regions enriched for different DNA repeats in the M. mirumnovem chromosomes. The size and localization of these regions varied in different copies of large chromosomes. They varied even in homologous chromosomes, suggesting their divergence due to genome re-diploidization after a WGD. Besides the newly formed chromosome regions enriched for DNA repeats, B chromosomes were found in the karyotypes of the studied specimens of M. mirumnovem. These B chromosomes varied in size and morphology. FISH with microdissected DNA probes revealed that some Bs had a distinct DNA content. FISH could paint differently B chromosomes in different worms and even in the same sample. B chromosomes could carry a bright specific fluorescent signal or could show no fluorescent signal at all. In latter cases, the specific FISH signal could be absent even in the pericentromeric region of the B chromosome. Possible mechanisms of B chromosome formation and their further evolution are discussed. The results obtained indicate an important role that repetitive DNAs play in genome re-diploidization initiating a rapid differentiation of large chromosome copies. Taking together, karyotype peculiarities (a high level of intraspecific karyotypic diversity associated with chromosome number variation, structural chromosomal rearrangements, and the formation of new regions enriched for DNA repeats) and some phenotypic features of M. mirumnovem (small body size, short lifecycle, easy maintenance in the laboratory) make this species a perspective model in the studies of genomic and karyotypic evolution in species passed through a recent WGD event.